How to develop effective communication skills - Brown, Rick; Heitz, Bill; Lucas, Robert W (Jack Wilson and Associates, 1990)
In this training program you will learn build trust so you can communicate openly and freely with others, remove barriers to positive communication, communicate nonverbally as well as verbally, develop better relationships through listening and deal with conflict in the work place.